Analysis of composition and microstructures of Ge grown on porous silicon using Raman spectroscopy and transmission electron microscopy. (December 2017) - Aouassa, Mansour; Jadli, Imen; Hassayoun, Latifa Slimen; Maaref, Hassen; Panczer, Gerard; Favre, Luc; Ronda, Antoine; Berbezier, Isabelle
Abstract: Composition and microstructure of Ge grown on porous silicon (PSi) by Molecular Beam Epitaxy (MBE) at different temperatures are examined using High Resolution Transmission Electron Microscopy (HRTEM) and Raman spectroscopy. Ge grown at 400 °C on PSi buffer produces a planar Ge film with high crystalline quality compared to Ge grown on bulk Si. This result is attributed to the compliant nature of PSi. Increasing growth temperature >600 °C, changes the PSi morphology, increase the Ge/Si intermixing in the pores during Ge growth and lead to obtain a composite SiGe/Si substrate. Ge content in the composite SiGe substrate can controlled via growth temperature. These substrates serve as low cost virtual substrate for high efficiency III–V/Si solar cells. Highlights: Ge grown at 400 °C on PSi buffer produces a planar Ge film with high crystalline quality compared to Ge grown on bulk Si. This result is attributed to the compliant nature of PSi. Increasing growth temperature >600 °C, changes the PSi morphology, increase the Ge/Si intermixing in the pores during Ge growth and lead to obtain a composite SiGe/Si substrate. Ge content in the composite SiGe substrate can controlled via growth temperature.